A) -2,8 * (-1) * (-1,1)=
b) -1,1 * (-11,1) * (-1,11)
c)-2 * (-4,4) * (-1) * (-3,3)
d)-2 1/3 * (-0,6) * 2 2/5 * (-1 1/9)
e)-3 3/4 * (-3 3/5) * (-0,625) * (-1,4)
f)-2 2/3 * (-1,5) * (-3 1/3 ) * (-0,6) * (-1)
g)- 8/3 * (-3,14) * (-1 5/7) * (-1) * [-(-14)]

a)-12 2/3 : 3 1/6 =
b) 4 1/6 : (-1 2/3)=
c)-6,3 :(-2,1)=
d)-6,8 :(-1,7)
e)-9,2 : (-0,05)=
f)-4,03:5=
g) 6,72: (-0,6)

plis pomóżcie !

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-18T19:02:26+01:00
A) -2,8 * (-1) * (-1,1)=2,8*(-1,1)=(-3.08)
b) -1,1 * (-11,1) * (-1,11)=13,5531
c)-2 * (-4,4) * (-1) * (-3,3)=29,04
d)-2 1/3 * (-0,6) * 2 2/5 * (-1 1/9)=(-7/3)*(-0,6)*12/5*(-10/9)=3,73333333
e)-3 3/4 * (-3 3/5) * (-0,625) * (-1,4)=-17/4*(-18/5)*(-0,625)*(-1,4)=13,3875
f)-2 2/3 * (-1,5) * (-3 1/3 ) * (-0,6) * (-1)=-8/3*(-1,5)*(-10/3)*(-0,6)*(-1)=-8
g)- 8/3 * (-3,14) * (-1 5/7) * (-1) * [-(-14)]=200,96

a)-12 2/3 : 3 1/6 =0.1111111111111111
b) 4 1/6 : (-1 2/3)=-2.5
c)-6,3 :(-2,1)=3
d)-6,8 :(-1,7)=4
e)-9,2 : (-0,05)=184
f) -4,03:5=-0,806
g)6,72: (-0,6)=-11,2
1 5 1
2009-11-18T19:06:25+01:00
A)-4,9
b)-23,3
c)-10,7
e)46,975
f)2,9
g)-61,6

a)2
b)308
c)-8,4
d)-8,5
e)-9,25
f)-0,806
g)6,12